Electrochemical synthesis to convert a Ag film into Ag nanoflowers with high electrocatalytic activity. Issue 50 (8th June 2017) - Chang, Ya-Huei; Liu, Chang; Rouvimov, Sergei; Luo, Tengfei; Feng, Shien-Ping
Abstract : A generic design rule is proposed to convert a Ag film into functional Ag nanocrystals via cyclic scanning electrodeposition. Abstract : The cyclic scanning electrodeposition method was proposed to convert a thin Ag film into nanocrystals (NCs) with various shapes including nanoflowers, nanorods, dendrites, decahedrons, and icosahedrons. The flower-like Ag NCs exhibit a remarkably enhanced catalytic activity for electro-oxidation of glucose.